Application of the RELATIVE scheme in the program of treatment of microcirculation disorders in patients with diabetes - O.A. Halushko; S.I. Babak (Civic Union "Communicable Diseases Intensive Care Association", 2022)
The work is devoted to the study of the effectiveness of the RELATIVE scheme (Reosorbilact, Latren, Tivortin) in patients with microcirculation disorders on the background of complicated diabetes mellitus. The study included 33 patients diagnosed with complicated diabetic foot syndrome. It was found that the use of complex infusion therapy according to the RELATIVE scheme for the treatment of microcirculation disorders in patients with diabetic foot syndrome helped to normalize blood glucose levels, improve patients' well-being, stabilize laboratory and biochemical parameters, reduce the severity of postoperative pain and the number of patients' complaints (insomnia, night pain, irritability and restlessness).